Program Lampionisasi Jalan Dusun Dan Pengembangan Produk Umkm Dalam Peningkatan Kreativitas Masyarakat Di Dusun Pundung Banaran Galur Kulon Progo - Wijayanto, Ari; Ilmi, Annisa Nurul; Hidayat, Putri Lathifah; Ma’rufah, Khairimatul; Iqmalia, Nindya Fani; Wardani, Pranesti Sanditiya; Darmawan, Muhammad Fahmi; Pratama, Muhammad Wahyu Diaz; Sandiaji, Alwi Farhan; Eryonaristobobamartyajati, Dhymasion Gusti; Suranto, Suranto (Universitas Muhammadiyah Yogyakarta, 2024)
One of the problems in Pundung Hamlet is the lack of street lighting, so the KKN 032 Program in Pundung Hamlet aims to solve the problem of street lighting with solar-powered PJU lights to increase security. In addition, teaching Family Medicinal Plants (TOGA) in elementary schools to add insight to children in elementary schools to add insight to children, socialization of Digital Marketing and UMKM rebranding, and socialization of Trap Barrier to increase agricultural yields. Activities took place January 11 - February 11, 2024, focusing on improving community welfare, knowledge, and skills. The methods used include preparation of work plans, program implementation, and evaluation. The survey results showed problems with street lighting and potential accidents. The solution is the use of solar-powered PJU lights. In addition, there are TOGA teaching activities in elementary schools, socialization of Digital Marketing and UMKM rebranding, and Trap Barrier socialization for farmers. Hopefully, this program will improve the welfare, business knowledge, and image of Pundung Hamlet, involving active participation of students in community development evenly and thoroughly.